Generalized Alexandroff Duplicates and CD 0(K) spaces - Çağlar, Mert; Ercan, Zafer; Polat, Faruk; ÇAĞLAR, MERT (My University, 2006)
We define and investigateCD Σ,Γ(K, E)-type spaces, which generalizeCD 0-type Banach lattices introduced in [1]. We state that the space CD Σ,Γ(K, E) can be represented as the space of E-valued continuous functions on the generalized Alexandroff Duplicate of K. As a corollary we obtain the main result of [6, 8].
Keywords: Alexandroff Duplicate; homeomorphism; Banach lattices; CD0(K, E)-spaces; 46D80; 54C35